Nilai Pendidikan Sosial Dalam Tari Moyo (Tari Elang) Pada Masyarakat Nias Di Kota Medan - Arvika Sari (Gesture: Jurnal Seni Tari, 2017)
This study aims to determine how the value of social education contained in Moyo Dance (Dance Eagle) on Nias people in the city of Medan.The theory used in this research is the theory of Hermin Kusumawati form of presentation, educational value of social theories of Edward Purba and Yusnadi. The method used is descriptive qualitative. The population in this study is the Nias community berurbanisasi to Medan. While the sample in this study is one of traditional artists from the studio Furai Nias, one singer, and 4 (four) dancers Moyo Dance (Dance Eagle). To complete the data in this study, researchers conducted a field observation, documentation in the form of videos and photographs and conduct interviews. The results based on the data collected can be seen that Moyo Dance (Dance Eagle) is a welcome dance performed by girls Nias to greet guests in the wedding. Moyo Dance (Dance Eagle), which developed in the city of Medan has entertainment functions of a commercial nature or as dance performances, because this dance is often performed for weddings. Shape Dance Moyo (Dance Eagle) in the city of Medan there are 10 varieties of motion is the motion the wing (mamologo afi), motion dealing (fatahő), motion disputing (Faonda), circles (sieligő), sight (fatahő) back, disputing ( Faonda), communicating (fahuhuo), pick (famaondragő), circles (sieligő), and then back (mangawei). Social educational value contained in Moyo Dance (Dance Eagle) is a sense of togetherness that is contained in the range of motion mamologo afi, faonda, and sieligő. A sense of ownership contained in the motion famaondragő. The sense of responsibility is seen in motion sieligődan famaondragő. Compactness seen from mamologo afi. And a sense of attachment and affection seen in motion fahuhu.